Greece : First and Second Reviews Under the Extended Arrangement Under the Extended Fund Facility, Request for Waiver of Applicability, Modification of Performance Criteria, and Rephasing of Access -- Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2013)
Greece's deep recession has continued unabated, with the economy struggling to gain traction against domestic political instability and weak external conditions. Stronger internal devaluation is now under way, reflecting the interaction of labor market liberalization with the already weak labor market. Current account adjustment has accelerated, notwithstanding slow progress with structural reforms. The structural transformation of Greece's economy continues to proceed at a slow pace, and this is making Greece's adjustment more costly. Institutional reforms continued to disappoint during 2012, again complicating overall adjustment efforts.